A rare case of adenoid cystic carcinoma of the trachea with literature review - Wierzbicka, Małgorzata; Nowak, Katarzyna; Kasprzyk, Mariusz; Szyfter, Witold; Banaszewski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
A rare case of adenoid cystic carcinoma of the upper part of the trachea with subglottic infiltration and oesophageal invasion is presented. Unique was the symptom which evoked the diagnostic steps – this 33-year-old man complained of shoulder pain playing tennis. The surgical procedure performed was total laryngectomy with 8 tracheal rings, partial oesophagectomy with free radial forearm flap reconstruction. A literature review concerning symptoms, tumour biology, treatment and prognosis of tracheal adenoid cystic carcinoma is presented.